The Influence of Company Size, Profitability, Leverage and Length of Listing on Intellectual Capital Disclosures - Gipson Guido Turnip; Nelvirita Nelvirita; Mayar Afriyenti (Universitas Negeri Padang, 2021)
This research explains and discuss the effect of company size, profitability, leverage and length of listing on intellectual capital disclosure in the annual report of manufacturing companies listed on the Bursa Efek Indonesia for period 2010 to 2013.The purpose of this research to empirically prove whether company size, profitability, leverage and length of listing on intellectual capital disclosures.This research uses quantitative method. Author quantifies the items of intellectual capital in the annual report to get the value’s independent variable. Meanwhile, the author calculates the natural logarithm on balance sheet as the size company variable, Return on Assets as the profitability variable, total debt to equity as the leverage variable, and calculated age company since listed on Bursa Efek Indonesia as length of listing variable.There are four items as the result of this research. First, company size does not affect the intellectual capital disclosures Second, profitability does not affect the intellectual capital disclosures. Third, company leverage has no effect on intellectual capital disclosures. The last, the length of listing has a significant positive effect on the intellectual capital disclosures